Bentuk Pertanggungjawaban Pidana Korporasi Sebagai Pelaku Tindak Pidana Dumping Limbah Bahan Berbahaya dan Beracun ke Media Lingkungan Hidup - Anton Wahyudi; Tofik Yanuar Chandra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
Protection of the environment is a must both for humans themselves. A corporation is a form of business entity which is run by humans to achieve their interests and gain profits. Environment and humans are 2 objects that are very dependent on each other. The integration between humans and the environment on the sustainability of human life itself, will affect various aspects of the Corporation in carrying out its business activities, so that it will affect the environmental system. Thus, the environment will certainly affect human life itself. One of the potentials in this crime is the crime of dumping hazardous waste, which in the nature of Law Number 32 of 2009 concerning Environmental Protection and Management, dumping of hazardous waste is prohibited if it is not managed. Protection of the environment is a must both for humans themselves. A corporation is a form of business entity which is run by humans to achieve their interests and gain profits.Keywords: Crime; Waste Dumping; Corporation